The Role of Global Commodity Prices in the Dynamics of the Business Cycle in Indonesia - Deswita Herlina; Doni Satria (Department of Development Economics, Universitas Sriwijaya, 2025)
This study examines the dynamic impact of global export commodity price fluctuations on the Indonesian economy, a representative small open economy with a significant reliance on primary resources. Using a Structural Vector Autoregression (SVAR) framework and quarterly data spanning from 1993 to 2019, the research analyzes the transmission of price shocks to the terms of trade, trade balance, and domestic business cycle variables, including per capita output, consumption, and investment. The empirical findings reveal that a positive shock to export commodity prices initially leads to a deterioration in the trade balance—consistent with the J-curve effect—due to the inelastic nature of imported industrial inputs and energy. However, the medium-term analysis identifies a significant